2011
DOI: 10.2134/agronj2011.0163
|View full text |Cite
|
Sign up to set email alerts
|

Soil Salinity and Quality of Sprinkler and Drip Irrigated Warm‐Season Turfgrasses

Abstract: A study was conducted in New Mexico from 2005 to 2007 to investigate the effects of two potable water‐saving strategies, irrigating with saline water and using subsurface systems, on changes in rootzone salinity and quality of nine warm‐season turfgrasses. Plots were irrigated using either sprinklers or subsurface drip with water of 1 of 3 salinity levels (0.6, 2.0, and 3.5 dS m−1). Plots were rated monthly for quality during the growing seasons and bi‐annually for spring and fall color. Soil samples were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
40
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 29 publications
(48 reference statements)
9
40
2
Order By: Relevance
“…Detailed information on soil properties, irrigation water salinity and sodicity, irrigation system uniformity and irrigation amounts for these research reports are listed in Table 2. The range of values reported in these studies underscores how numerous factors, such as climate and irrigation (precipitation, leaching fraction), soil type and original soil salinity, salinity of irrigation water, and system distribution uniformity, all influence and contribute to changes in soil salinity following irrigation with saline water (Devitt et al, 2007;Ganjegunte et al, 2013;Qian and Mecham, 2005;Schiavon et al, 2014;Sevostianova et al, 2011aSevostianova et al, , 2011bThomas et al, 2006). Developing appropriate salinity management and remediation strategies requires detailed information on the distribution of salinity (EC e ) within the turf root zone.…”
Section: Soil Salinity Of An Urban Park After Long-termmentioning
confidence: 91%
See 3 more Smart Citations
“…Detailed information on soil properties, irrigation water salinity and sodicity, irrigation system uniformity and irrigation amounts for these research reports are listed in Table 2. The range of values reported in these studies underscores how numerous factors, such as climate and irrigation (precipitation, leaching fraction), soil type and original soil salinity, salinity of irrigation water, and system distribution uniformity, all influence and contribute to changes in soil salinity following irrigation with saline water (Devitt et al, 2007;Ganjegunte et al, 2013;Qian and Mecham, 2005;Schiavon et al, 2014;Sevostianova et al, 2011aSevostianova et al, , 2011bThomas et al, 2006). Developing appropriate salinity management and remediation strategies requires detailed information on the distribution of salinity (EC e ) within the turf root zone.…”
Section: Soil Salinity Of An Urban Park After Long-termmentioning
confidence: 91%
“…Water sample analyses indicated that irrigation water although saline (C3-S1 as per Richards, 1954) was of relatively better quality (lower salinity and sodicity) than the salinity values reported for other ground waters in the area used for irrigation (Schiavon et al, 2014;Sevostianova et al, 2011aSevostianova et al, , 2011b. The Chamizal Memorial is located on the Rio Grande river flood plain and ground water is derived from freshwater zone of the Rio Grande Aquifer.…”
Section: Irrigation Water Quality Apparent Electrical Conductivity Dmentioning
confidence: 96%
See 2 more Smart Citations
“…Based on these studies, the logical conclusion would be that warm-season grasses should be grown in areas affected by drought and where the use of saline water for irrigation is encouraged. Until recently, the use of warm-season grasses in transition zone climates had been difficult because their growing season barely exceeds 6 mo (Sevostianova et al, 2011b). However, a shorter growing season and the associated shorter irrigation period results in less water needed to maintain turf areas.…”
mentioning
confidence: 99%